2021
DOI: 10.3310/hsdr09190
|View full text |Cite
|
Sign up to set email alerts
|

Care home residents’ quality of life and its association with CQC ratings and workforce issues: the MiCareHQ mixed-methods study

Abstract: Background Care home staff have a critical bearing on quality. The staff employed, the training they receive and how well they identify and manage residents’ needs are likely to influence outcomes. The Care Act 2014 (Great Britain. The Care Act 2014. London: The Stationery Office; 2014) requires services to improve ‘well-being’, but many residents cannot self-report and are at risk of exclusion from giving their views. The Adult Social Care Outcomes Toolkit enables social care-related quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 281 publications
(416 reference statements)
7
41
0
Order By: Relevance
“…This suggests there is still a further need for methodological innovation to promote their inclusion in service evaluation. One approach that may have merit is the multi‐methods ASCOT CH4 54 —which has been used to promote greater inclusion of the voice of older people with cognitive and communication impairment living in institutional/care home settings but has not yet been feasible in a community setting.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests there is still a further need for methodological innovation to promote their inclusion in service evaluation. One approach that may have merit is the multi‐methods ASCOT CH4 54 —which has been used to promote greater inclusion of the voice of older people with cognitive and communication impairment living in institutional/care home settings but has not yet been feasible in a community setting.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns also relate to the effect that staff shortages have on providers’ performance. Employees’ turnover and vacancies in LTC are much higher than in other industries and evidence has shown that low staffing levels impact the quality of services (Allan and Vadean, 2021; Towers et al, 2021).…”
Section: Stagnating Numbers Of Carersmentioning
confidence: 99%
“…Turnover requires hiring replacement staff, which entails recruitment costs and generates periods of understaffing. Furthermore, high turnover, as well as high staff vacancies, have proven to negatively impact the quality of care (Allan and Vadean, 2021; Towers et al, 2021).…”
Section: Poor Working Conditions Limit Recruitment and Retention Of L...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of turnover rates in the LTC sector have provided valuable insights and highlighted their association with factors such as ownership structure ( 3 5 ), management style ( 6 , 7 ), job satisfaction and employment conditions ( 8 , 9 ). Related work has also found that staff turnover is associated with quality of care measures ( 2 , 10 14 ). Nevertheless, turnover forms only part of the picture because the impact of staff turnover on the care workforce is mediated by care providers' ability to replace leavers through recruitment.…”
Section: Introductionmentioning
confidence: 98%